2014
DOI: 10.1063/1.4894815
|View full text |Cite
|
Sign up to set email alerts
|

Non uniform shrinkages of double-walled carbon nanotube as induced by electron beam irradiation

Abstract: Electron beam-induced nanoinstabilities of pristine double-walled carbon nanotubes (DWCNTs) of two different configurations, one fixed at both ends and another fixed at only one end, were in-situ investigated in transmission electron microscope at room temperature. It was observed that the DWCNT fixed at both ends shrank in its diameter uniformly. Meanwhile, the DWCNT fixed at only one end intriguingly shrank preferentially from its free cap end along its axial direction whereas its diameter shrinkage was offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Moreover, the wire universally showed a preferential axial shrinkage from the free end no matter whether it is with sharp cut edge or of hemisphere shape. Similar axial shrinkages preferentially from the free end were also observed in carbon nanotubes [15,16] as a universal phenomenon. All of these indicated that the nanocurvature effect dominated or governed the dynamics of surface diffusion and evaporation of atoms.…”
Section: Resultssupporting
confidence: 77%
“…Moreover, the wire universally showed a preferential axial shrinkage from the free end no matter whether it is with sharp cut edge or of hemisphere shape. Similar axial shrinkages preferentially from the free end were also observed in carbon nanotubes [15,16] as a universal phenomenon. All of these indicated that the nanocurvature effect dominated or governed the dynamics of surface diffusion and evaporation of atoms.…”
Section: Resultssupporting
confidence: 77%
“…In fact, our previous work on the energetic beam irradiation-induced structural instabilities and processing of low dimensional nanostructures (LDNs), such as nanocavities in Si [16,[28][29][30][31], carbon nanotubes [32,33] and amorphous SiOx nanowires [22,34], has proven that our proposed nanocurvature effect [16,17] and energetic beam-induced athermal activation effect [16,18] For the nanocurvature effect on a nanowire, we can suppose that, similar to the particle case [16,17], when the diameter of a nanowire reduces down to nanoscale and can be comparable to its atomic bond length, a positive nanocurvature on the highly curved wire surface will become appreciable, as shown in Fig. 3(a).…”
Section: Resultsmentioning
confidence: 99%
“…The previous research [1][2]4,[12][13][14] has demonstrated that our proposed nanocurvature effect [4][5] and beam-induced atomic vibration soft mode and instability effect [3][4] are universal concepts and can well explain the beam-induced nanophenomena. From the following analysis, we can conclude that the nanocurvature effect of the a-SiOx NW and the e-beam-induced atomic vibration soft mode and instability effect are the two key factors to induce the observed comparasive structural changes of the a-SiOx NWs.…”
Section: Resultsmentioning
confidence: 99%